Copy number variation - Gökçümen, Ömer (Henry Stewart Talks, 2009)
Copy Number Variants (CNVs), Widespread structural variation among healthy humans, Methods to detect CNVs, Current state of CNV research, Ongoing studies to characterize evolution and global distribution of CNVs